Association between academic perfomance and eating habits - Cortez Gutiérrez, Hernán Óscar; Cortez Gutiérrez, Milton Milcíades; Grados Gamarra, Juan Herber; Rubiños Jiménez, Santiago Linder; Espinoza Flores, Braulio Pedro (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The objective of our research is to determine the impact of eating habits on academic performance. Eating habits were evaluated according to validated instruments and their normality was established with Shapiro-Wilk W=0.97 and significance p-value=0.34. We have that food consumption also has a normal distributionand impacts on academic performance with a Pearson correlation of 0.24 andsignificance p-value=0.04. The logistic regression establishes the consumption cut-off point equal to 38 to have a 50% probability of good academic performance.Likewise, the punctual estimate of academic performance corresponding to this cutof consumption 38 is the score of 14.